Poland in the European Union: Successes and Failures of the First Decade (2004–2014) (Economic and Political Thought, 2014)
The article aims to present the effects of the accession of Poland to theEuropean Union against a broader background of international relations andthe context of changes that took place in the EU in the last decade. Thus,we deal with a specific balance of successes and failures Poland experiencedin the period 2004–2014. The article shows that, twenty-five years after thepolitical transformation in Poland and ten years after the accession to theEuropean Union, our membership in that specific, voluntarily integratedunion of sovereign European states undoubtedly proved to be necessary andinevitable. Thus, it is the basic thesis of this article. It was the only appropriatesolution for Poland that resulted from its geopolitical location and historicalexperiences. Against all odds, it has not harmed our sovereignty and nationalidentity. The author emphasises that the membership in the European Unionhas strengthened Poland’s sovereignty and serves Polish national interest. Ithas a positive impact on Poland’s economy and strengthens its prestige onthe international arena.